2015
DOI: 10.4314/sajg.v4i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing-based fire frequency mapping in a savannah rangeland

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Since the 1970s, researchers have considered this area of research to be particularly significant [7,12], and since 1990, numerous studies have been published assessing the contribution of pyrogenic greenhouse gas emissions to total anthropogenic emissions [6,7,[13][14][15]. Estimates now exist for carbon emissions from fires in tropical [15,16] and boreal forests [6,10,14,[17][18][19][20][21], African [22][23][24] and Australian [25] savannas, and steppe regions [26,27]. Numerous works are likewise devoted to assessing the scale and impact of wildfires in the boreal zone of the Northern Hemisphere [10,[19][20][21]28]; however, most authors focus primarily on forestry [10,14,19,20,[29][30][31] and peat fires [32,33], as well as the consequences of agricultural burns in North America [34], Eastern Europe [34][35][36][37], and Asia [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970s, researchers have considered this area of research to be particularly significant [7,12], and since 1990, numerous studies have been published assessing the contribution of pyrogenic greenhouse gas emissions to total anthropogenic emissions [6,7,[13][14][15]. Estimates now exist for carbon emissions from fires in tropical [15,16] and boreal forests [6,10,14,[17][18][19][20][21], African [22][23][24] and Australian [25] savannas, and steppe regions [26,27]. Numerous works are likewise devoted to assessing the scale and impact of wildfires in the boreal zone of the Northern Hemisphere [10,[19][20][21]28]; however, most authors focus primarily on forestry [10,14,19,20,[29][30][31] and peat fires [32,33], as well as the consequences of agricultural burns in North America [34], Eastern Europe [34][35][36][37], and Asia [38].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, such studies inadequately cover meadow and meadow-mire ecosystems, in which fires are characterized by low carbon emissions (when compared to forest ones) [28] but are very frequent due to the significant accumulation of combustible substances. Their characteristic feature is the presence of two 'fire hazard' seasons; this distinguishes meadows of the Russian Far East from Australian bush and African savannas, which are otherwise comparable in terms of the mass of combustible plant material [22,24]. The first period of herb drying is in spring, from the snowmelt until the beginning of active plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies of long-term trends and interannual variability of fires found large year-to-year changes associated with extreme climate conditions (Chen et al, 2013). Combined with climate, fuel moisture and fuel type, which are characteristics of the vegetation, are dependent variables of the ignition and spread of fires (Leblon et al, 2012). Variations in vegetation condition, which can be expressed by vegetation indices, are an important indicator of stress factors for plants, such as drought, and are useful for assessing the susceptibility of vegetation to fires (Bajocco et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the orbital sensors available for studying fires, Moderate Resolution Imaging Spectroradiometer (MODIS) active fire and burned area products were the first data sets derived from the new generation of moderate resolution orbital sensors (Giglio et al, 2016) and have been widely used to understand the role and characteristics of fires and biomass burning (Ichoku et al, 2005;Kaiser et al, 2012;Hantson et al, 2013;Shi et al, 2015;Shvetsov and Ponomarev, 2015;Huang et al, 2016). Regarding the tropical savannas, we can mention the use of MODIS active fire and burned area products to analyse fires in the savannas of Brazil (Nascimento et al, 2010;Moreira de Araújo et al, 2012; Moreira de Araújo and Ferreira, 2015), Africa (Archibald et al, 2010;Kusangaya and Sithole 2015), Australia (Andersen et al, 2005;Yates et al, 2008;Maier et al, 2013), and in the entire tropical savannas (Van der Werf et al, 2008).…”
Section: Introductionmentioning
confidence: 99%